Soft Skill and Entrepreneurial Career Guidance Model for Enhancing Technical Vocational Education and Training’s Graduates Competitiveness - Dardiri, Ahmad (INVOTEC, 2016)
The globalization and free trade era have implications for the high competition for vocational institutions. Problems faced by vocational education are (1) lack of relevance of the graduates competence with the industrial need, (2) low absorption of the graduates by industry, (3) discrepancy of skill competencies program that developed with the needs of industry, (4) there is lack understanding of the vision mission and objectives of vocational education among practitioners in the industry, (5) learning infrastructure gaps with industrial need, (6) absence of career standardization structure development on industry, and (7) unfavorable the academic climate in vocational education. Facing these challenges is necessary required soft skills and entrepreneurial career guidance model as solutions to enhance the graduate competitiveness.